Tradition and New Challenges for the HLT Community - Vetulani, Zygmunt (Studia Informatica. System and information technology, 2006)
The domain of Human Language Technologies is a fascinating and challenging area of research and development. We introduce the reader into this domain, present its tradition and recent challenges.